A kinesin‐based approach for inducing chromosome‐specific mis‐segregation in human cells - My Anh Truong; Paula Cané‐Gasull; Sippe G. de Vries; Wilco Nijenhuis; René Wardenaar; Lukas C. Kapitein; Floris Foijer; Susanne M.A. Lens (2023)
Abstract Various cancer types exhibit characteristic and recurrent aneuploidy patterns. The origins of these cancer type‐specific karyotypes are still unknown, partly because introducing or eliminating specific chromosomes in human cells still poses a challenge. Here, we describe a novel strategy to induce mis‐segregation of specific chromosomes in different human cell types. We employed Tet repressor or nuclease‐dead Cas9 to link a microtubule minus‐end‐directed kinesin (Kinesin14VIb) from Physcomitrella patens to integrated Tet operon repeats and chromosome‐specific endogenous repeats, respectively. By live‐ and fixed‐cell imaging, we observed poleward movement of the targeted loci during (pro)metaphase. Kinesin14VIb‐mediated pulling forces on the targeted chromosome were counteracted by forces from kinetochore‐attached microtubules. This tug‐of‐war resulted in chromosome‐specific segregation errors during anaphase and revealed that spindle forces can heavily stretch chromosomal arms. By single‐cell whole‐genome sequencing, we established that kinesin‐induced targeted mis‐segregations predominantly result in chromosomal arm aneuploidies after a single cell division. Our kinesin‐based strategy opens the possibility to investigate the immediate cellular responses to specific aneuploidies in different cell types; an important step toward understanding how tissue‐specific aneuploidy patterns evolve.